1990
DOI: 10.1152/jappl.1990.68.5.2034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sleep on lung volume in asthmatic patients and normal subjects

Abstract: To assess the effect of sleep on functional residual capacity (FRC) in normal subjects and asthmatic patients, 10 adult subjects (5 asthmatic patients with nocturnal worsening, 5 normal controls) were monitored overnight in a horizontal volume-displacement body plethysmograph. With the use of a single inspiratory occlusion technique, we determined that when supine and awake, asthmatic patients were hyperinflated relative to normal controls (FRC = 3.46 +/- 0.18 and 2.95 +/- 0.13 liters, respectively; P less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
1
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(92 citation statements)
references
References 0 publications
4
84
1
3
Order By: Relevance
“…38 Patients with nocturnal asthma, who start the night hyperinflated relative to controls, experience an augmented decline in functional residual capacity (FRC) to levels comparable to those of control subjects during REM sleep. 39 It is thus possible that the improved lung mechanics with FP also attenuated the degree of decline in FRC during sleep; the resultant increase in pharyngeal UAW tethering via tracheal tug could have rendered it stiffer, 40 thereby also improving the Pcrit. Further studies accounting for nasal resistance and sleep related changes in lower airway mechanics will be needed; (2) an unchanged Pcrit could result from above changes being offset by deleterious effects, discussed next; (3) a deterioration in Pcrit could result from a predominant increase in the surrounding tissue pressure, including fat accumulation, and from changes in the properties of UAW muscle, as suggested by our findings on the tongue discussed below.…”
Section: Patterns Of Pcrit Responses To Fp Therapy and Possible Explamentioning
confidence: 99%
“…38 Patients with nocturnal asthma, who start the night hyperinflated relative to controls, experience an augmented decline in functional residual capacity (FRC) to levels comparable to those of control subjects during REM sleep. 39 It is thus possible that the improved lung mechanics with FP also attenuated the degree of decline in FRC during sleep; the resultant increase in pharyngeal UAW tethering via tracheal tug could have rendered it stiffer, 40 thereby also improving the Pcrit. Further studies accounting for nasal resistance and sleep related changes in lower airway mechanics will be needed; (2) an unchanged Pcrit could result from above changes being offset by deleterious effects, discussed next; (3) a deterioration in Pcrit could result from a predominant increase in the surrounding tissue pressure, including fat accumulation, and from changes in the properties of UAW muscle, as suggested by our findings on the tongue discussed below.…”
Section: Patterns Of Pcrit Responses To Fp Therapy and Possible Explamentioning
confidence: 99%
“…BALLARD et al [48] showed that, while the FRC of patients with mild asthma when awake was greater than control subjects, during sleep the fall in FRC exceeded that in normals, so that during rapid eye movement (REM) sleep FRC was similar in the two groups ( fig. 5a).…”
Section: Sleepmentioning
confidence: 99%
“…[2][3][4][5] During sleep, in normal subjects, upper airway resistance increases and functional residual capacity decreases. [6][7][8] This sleep induced decrease in lung volume is believed to result in increased upper airway collapsibility and to contribute to inspiratory flow limitation, although the exact mechanisms have not been delineated. Animal data using mongrel dogs have suggested that thoracic inflation increases upper airway pharyngeal size and stiffness through caudal traction on the trachea independently of upper airway muscle activity.…”
mentioning
confidence: 99%